Obstacles for school garden program success: Expert consensus to inform policy and practice. Issue 3 (3rd July 2019) - Diaz, John M.; Warner, Laura A.; Webb, Susan; Barry, Debra
ABSTRACT: Perceptions of the potential of school gardens are changing given the pressing need to increase food security, environmental protection, livelihood security, and nutrition. Although school gardens programs appear positioned to become fixtures in educational institutions, there are still a number of impediments that need to be addressed to ensure their success in supplementing education. The purpose of this study was to demonstrate a consensus-driven process to identify the central issues impeding the sustained success of school gardens. We outline practical, logistical, and institutional barriers that may assist in refining support of school gardens for sustained success.